“I Need More Practices”: Exploring Difficulties Faced by EFL Students in Practicing Interpreting - Pratama, Ikke Dewi; Rohmatika, Arina (Universitas Negeri Semarang, 2025)
As one of the branches in translation studies, interpreting is an interesting, yet a complex, spoken translation activities. The needs to master comprehensive skills leave challenges in studying interpreting even for students whose major is in English department. This is a qualitative case study research which aims at analyzing difficulties encountered by the students when practicing consecutive interpreting. The data were obtained through open-ended questionnaire which was distributed to 35 students taking Interpreting for the MICE Industry as an obligatory course. The data were analyzed through thematic analysis. It was found out that the students faced difficulties related to: (1) the students’ views on the interpreters’ job, (2) the speakers’ speech, (3) the students’ interpreting skill, and (4) the students’ hesitation. This research also proposes alternatives for interpreting lecturers to cope with difficulties faced by the students when studying interpreting. Since problems are usually encountered by interpreting students when practicing consecutive interpreting, the findings of the research can be insightful resources for lecturers to develop more effective interpreting syllabus and media.